The Effectiveness of Health Education on the Motivation to Quit Smoking in the Islamic Boarding School Students in Aceh - Ismail Ismail; Rapitos Siddiq; Bustami Bustami (Health Notions, 2021)
Introduction: The phenomenon of smoking in the pesantren shows that almost all students studying at the pesantren smoke. There is no regulation that states that smoking is prohibited and that makes them free to smoke. Sufficient knowledge about the dangers of smoking to health can motivate people to quit smoking. Motivation can be done in various ways, one of which is by using audiovisual media. Objective: To determine the effectiveness of audio-visual health education about the dangers of smoking on the motivation to quit smoking in the Islamic boarding school students in Aceh. Methods: The research design was a quasy experimental pretest-posttest with control group design, involving 38 participants for the intervention group and 38 participants for the control group. Data analyzed by paired sample t-test and independent sample t-test. Results: There was no difference in the average motivation to quit smoking before the intervention group was given to the intervention group and the control group (p = 0,664). The intervention group was more effective at increasing the students' motivation to quit smoking compared to the control group (p = 0.027). Conclusion: Health education using audiovisuals was more effective in increasing the motivation of the students to quit smoking, so that audiovisuals can be used during health education. Keywords: health education; audiovisual; motivation to quit smoking